Juridical Analysis of Police Discretion on Traffic Violations by Children of Motorists Going to School Without a Driver's License (SIM) - Yasnil Akbar Nasution; Yasmirah Mandasari Saragih (International Journal of Society and Law, 2024)
Motorcycles have become an important part of Indonesia's life, but their use by minors who do not yet have a Driver's License (SIM) poses a high risk. This phenomenon shows that there is a social deviation triggered by weak parental and community control. Law Number 22 of 2009 regulates the obligation to have a driver's license for motorists, but many children still drive motorcycles. In this context, police discretion is important, where the police have the authority to make decisions based on the existing situation. This study aims to analyze the implementation of police discretion against traffic violations by school children who ride motorcycles without a driver's license, as well as identify obstacles in the implementation of such discretion. The results of the research are expected to provide insight into the challenges faced in law enforcement and increase legal awareness in the community, so as to create safe and orderly traffic.